Effect of a blend of essential oils, organic acids, tannins, vitamin E and zinc on the intestinal health of broiler chickens challenged with Eimeria spp., Salmonella Minnesota, Escherichia coli and Clostridium perfringens - Leila S. Tolomeotti; Rafael H.T.B. Goes; Gabriela H. Cangianelli; Angélica S. Khatlab; Keila M. Pontes; Evandro B. Matos; Ana Paula Del Vesco; Stefano Miglioranza; Eliane Gasparino (Pesquisa Veterinária Brasileira)
ABSTRACT: This study aimed to evaluate the effects of (i) diets supplemented with a blend of organic acids, cinnamon essential oil, oregano essential oil, eugenol, thymol, curcumin, tannins, vitamin E, and zinc microencapsulated in vegetable fat and (ii) a challenge by Eimeria spp., Salmonella Minnesota, Escherichia coli, and Clostridium perfringens. Also, to evaluate the diet × challenge interaction effects on animal performance (1-21 and 22-42 days of age), weights of organs and primal cuts, and ileal morphometry in 42-day-old broiler chickens. The experiment was conducted according to a 2 × 2 factorial design (supplemented and unsupplemented diets × challenged and unchallenged broilers). Each treatment consisted of eight replications and eight birds per replicate. At 14 days of age, chickens in the challenge group (n=128) received orally 1mL of a suspension containing sporulated oocysts of Eimeria spp. (E. acervulina, E. praecox, E. maxima, E. mitis, E. tenella, and E. necatrix), and the other experimental group (n=128) received 1mL of saline solution orally. At 18 days of age, birds in the challenge group received 1mL of a suspension of C. perfringens, E. coli, and S. Minnesota, and unchallenged birds received 1mL of saline solution orally. From 1 to 21 days of age, microbial challenge reduced body weight, feed intake, weight gain and increased feed conversion. In the same period, supplemented birds had lower feed conversion. From 22 to 42 days of age, challenged birds had lower body weight, feed conversion, breast weight, thigh + drumstick weight, and heart weight. Supplemented birds had higher breast weight. Unchallenged birds fed the supplemented diet showed higher bursa weight, proventriculus weight, ileal villus height, and crypt depth. Unchallenged birds fed the unsupplemented diet had higher liver weight. Microbial challenges with Eimeria spp., S. Minnesota, C. perfringens, and E. coli impaired productive performance in the starter phase. They decreased the yield of primal cuts in 42-day-old broilers, partially explaining the recurring economic problems observed in the poultry sector. Overall, the studied blend was able to improve feed conversion in the starter phase, enhance digestive and absorption processes, and increase the yield of primal cuts. However, no effects were observed in challenged birds. The findings suggest that the studied effects are influenced by microbial conditions, blend composition, and inclusion level and may or may not result in beneficial outcomes.